2003
DOI: 10.1016/s0730-725x(03)00128-0
|View full text |Cite
|
Sign up to set email alerts
|

Pore surface exploration by NMR

Abstract: A carefully chosen set of experimental techniques applied to porous media characterisation provides results that can be much greater than the sum of the individual parts. The inter-relation and complementarity of a number of techniques will be considered. NMR cryoporometry provides a valuable method of pore size measurement. An NMR method that is more widely used to assess pore dimensions relies on relaxation time analysis of a liquid that fills the pores and the enhanced relaxation that occurs in a liquid at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 19 publications
3
58
0
Order By: Relevance
“…FID and single spin echoes are suited to the former method, whereas spin echo trains are better acquired using the latter method. NMR cryoporometry experiments can also be performed using absorbates with bulk melting points above ambient temperature (Strange et al, 2003). This makes the experiment easier to perform and less costly without requiring the use of cryogens.…”
Section: The Nmr Cryoporometry Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…FID and single spin echoes are suited to the former method, whereas spin echo trains are better acquired using the latter method. NMR cryoporometry experiments can also be performed using absorbates with bulk melting points above ambient temperature (Strange et al, 2003). This makes the experiment easier to perform and less costly without requiring the use of cryogens.…”
Section: The Nmr Cryoporometry Measurementmentioning
confidence: 99%
“…In recent work, octamethylcyclotetrasiloxane was seen to have a larger melting point depression constant than cyclohexane, potentially allowing access to pores of greater than 1 µm diameter . Naphthalene, used for super-ambient NMR cryoporometry with a bulk melting point of T ∞ m = 354 K, was determined to have a melting point depression constant of k GT = 181 K nm by NMR and DSC measurements (Strange et al, 2003). Octaphenylcyclotetrasiloxane has also been suggested for high-temperature NMR cryoporometry (T ∞ m = 473 K) although this has not yet been successfully demonstrated as a potential absorbate (Mitchell, 2003).…”
Section: Calibrationmentioning
confidence: 99%
“…It has been shown elsewhere that water has a far stronger affinity to the surface in these silicas than nonpolar organic liquids 5 . This is because the silica surface contains hydroxyl groups to which the water molecules can form hydrogen bonds.…”
Section: Resultsmentioning
confidence: 92%
“…The most frequently used NMR technique has been relaxometry 3 . Although this method can provide estimates of the pore size distributions in the rocks 4 , it is highly sensitive to surface interactions 5 and can be difficult to interpret accurately 6 . Diffusion studies of flowing systems using NMR Pulsed Field Gradient (PFG) 7 measurements have shown how water can partially displace oil from rock pores.…”
Section: Introductionmentioning
confidence: 99%
“…Water can be frozen in narrower pores (cavities in biomacromolecules, RBC membrane, intracellular space or voids between primary particles of nanooxides) at lower temperature that can be described by the Gibbs-Thomson relation for the freezing point depression [18,24,[30][31][32][33] …”
Section: Tablementioning
confidence: 99%